An Air‐ and Water‐Stable B4N4‐Heteropentalene Serving as a Host Material for a Phosphorescent OLED. Issue 44 (23rd September 2021) - Kashida, Junki; Shoji, Yoshiaki; Ikabata, Yasuhiro; Taka, Hideo; Sakai, Hayato; Hasobe, Taku; Nakai, Hiromi; Fukushima, Takanori
Abstract: Replacement of the carbon–carbon bonds of antiaromatic compounds with polar boron–nitrogen bonds often provides isoelectronic BN compounds with excellent thermodynamic stability and interesting photophysical properties. By this element‐substitution strategy, we synthesized a new B4 N4 ‐heteropentalene derivative, 1, which is fully substituted with mesityl groups. Owing to kinetic protection by the sterically bulky substituents, 1 is remarkably stable toward air and even water. Single‐crystal X‐ray analysis of 1 revealed the bonding characteristics of the B4 N4 ‐heteropentalene structure. In a glassy matrix, 1 emitted short‐wavelength phosphorescence with an onset at 350 nm, indicating that the triplet energy is substantially high. DFT calculations reasonably explained the ground‐ and excited‐state electronic structures of 1 as well as its emission properties. Motivated by the high‐energy triplet state of 1, we used it as a host material to fabricate a phosphorescent organic light‐emitting diode with an external quantum efficiency of 15 %. Abstract : A B4 N4 ‐heteropentalene (see structure) featuring a large HOMO–LUMO gap was synthesized and found to exhibit excellent thermal and chemical stability. The compound has a high T1 energy and can therefore emit short‐wavelength phosphorescence comparable to that of benzene. Owing to its photophysical properties, the B4 N4 ‐heteropentalene served as a good host material for a phosphorescent organic light‐emitting diode.